Self-compassion, resilience and psychological well-being among Malaysian counsellors / Voon Siok Ping - Voon , Siok Ping (2019)

(untitled)
In line with the movement of self-care for both counsellor practitioners and educators, the present study was conducted with the intention to investigate the relationship between self-compassion, resilience and psychological well-being among registered counsellors in Malaysia. Besides, the current research examined the mediating effect of resilience and moderating effects of gender and year of experience on counsellors‘ psychological well-being. This study was a cross-sectional quantitative research and data was collected via web-based survey. Based on the list of registered counsellors obtained from the Malaysian Board of Counsellor, an invitation email with the link accessible to the questionnaire was sent and participation was on voluntary basis. Three instruments namely the Self-Compassion Scale, the Connor-Davidson Resilience Scale and the Scale of Psychological Well-Being were utilized. All three instruments reported satisfactory reliability, with CR value of .858 (self-compassion), .908 (resilience) and .898 (psychological well-being). A total of 408 participants were involved in this study, comprising 109 male counsellors and 299 female counsellors from the 13 states and 2 federal territories of Malaysia. The descriptive analysis showed that, as a group, registered counsellors in Malaysia exhibited high overall self-compassion (M=101.16), high resilience (M=33.26) and high overall psychological well-being (M=198.21). PLS-SEM served as the main data analysis method for this study, specifically, the Smart-PLS 3.0 software was employed. The inferential analysis demonstrated that (a) self-compassion was significantly and positively related to psychological well-being, β = .499, p < .001; (b) self-compassion was significantly and positively related to resilience, β = .639, p < .001; (c) resilience was significantly and positively related to psychological well-being, β = .366, p < .001; (d) there was a significant mediating effect of resilience on self-compassion and psychological wellbeing, β = .234, p < .001, (e) there was a significant moderating effect of gender on self-compassion and psychological well-being, β = .066, p < .05, with stronger relationship reported for female counsellors while there was no significant moderating effect of gender on resilience and psychological well-being β = -.192, p > .05, (f) there were no significant moderating effect of year of experience for both self-compassion, resilience and psychological well-being, with β = .003, p > .05 and β = -.013, p > .05 respectively. Results also revealed that self-compassion has a large effect on counsellors‘ resilience and psychological well-being whereas resilience has a medium effect on counsellors‘ psychological well-being. Overall, the research model explained a substantial amount of variance (61.6%) in counsellors‘ psychological well-being. As evidenced by the empirical findings of this study, the hypothesized model holds true that self-compassion and resilience related to counsellors‘ psychological well-being. This study has highlighted the two important human factors, i.e. selfcompassion and resilience in the development of counsellors‘ psychological wellbeing. Notwithstanding the limitations of this study, the current research has provided invaluable theoretical, practical and research implications. Self-compassion appeared to be a valid and influential construct in enhancing counsellors‘ resilience and psychological well-being in Eastern setting. Integrating self-compassion and resilience is of central importance in cultivating well-being among counsellors in Malaysia.